2022
DOI: 10.1038/s41598-022-24147-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of alternative mRNA splicing in cultured cell populations representing progressive stages of human fetal kidney development

Abstract: Nephrons are the functional units of the kidney. During kidney development, cells from the cap mesenchyme—a transient kidney-specific progenitor state—undergo a mesenchymal to epithelial transition (MET) and subsequently differentiate into the various epithelial cell types that create the tubular structures of the nephron. Faults in this transition can lead to a pediatric malignancy of the kidney called Wilms’ tumor that mimics normal kidney development. While human kidney development has been characterized at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The most prominent motif enrichment was found for the RNA binding proteins RBFOX1 [55,63] and QKI [55,63,64], which indicates that in the more stromal tumors, these splicing regulators are over-expressed and tend to bind downstream of their target exons and promote their inclusion. We note that RBFOX1 and QKI were previously shown to physically interact with each other in order to regulate alternative splicing in mammary epithelial cells, thereby promoting an epithelial to mesenchymal transition (EMT) [55], and have also been associated with the mesenchymal to epithelial transition (MET) that occurs during fetal kidney development [35].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent motif enrichment was found for the RNA binding proteins RBFOX1 [55,63] and QKI [55,63,64], which indicates that in the more stromal tumors, these splicing regulators are over-expressed and tend to bind downstream of their target exons and promote their inclusion. We note that RBFOX1 and QKI were previously shown to physically interact with each other in order to regulate alternative splicing in mammary epithelial cells, thereby promoting an epithelial to mesenchymal transition (EMT) [55], and have also been associated with the mesenchymal to epithelial transition (MET) that occurs during fetal kidney development [35].…”
Section: Resultsmentioning
confidence: 99%
“…Specifically in Wilms’ tumor, a recent study showed that the splicing regulator ESRP2 is repressed by DNA methylation, whereas over-expression of ESRP2 in Wilms’ tumor cell lines promotes alternative splicing and inhibits cell proliferation both in-vitro and in-vivo [34]. In a recent work, we also found that fetal kidney cells at an early developmental stage have a mesenchymal splice-isoform profile that is similar to that of blastemal-predominant Wilms’ tumor xenografts [35]. Therefore, analysis of alternative splicing in different subtypes of Wilms’ tumors could provide insights to the molecular processes driving tumor development and their relation to kidney development.…”
Section: Introductionmentioning
confidence: 94%
“…The findings exhibited a sequential decline in mesenchymal-associated gene expression and a simultaneous increase in epithelial-associated gene expression during fetal kidney development. In contrast, the WT samples exhibited elevated expression levels of mesenchymal-associated genes and relatively reduced expression levels of epithelial-associated genes ( Wineberg et al, 2022 ). We postulate that the low expression levels of AQP1 in WT may inhibited the process of MET, while the overexpression of AQP1 may potentially reduce the formation of mesenchymal in cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work, we also found that fetal kidney cells in an early developmental stage have a mesenchymal splice-isoform profile that is similar to that of blastemal-predominant Wilms' tumor xenografts [40]. However, a comprehensive analysis of alternative splicing in high-risk Wilms' tumors is lacking, and could provide insights into the molecular processes driving tumor development and their relation to kidney development.…”
Section: Introductionmentioning
confidence: 89%
“…The most prominent motif enrichment was found for the RNA binding proteins RBFOX1 [62,70] and QKI [62,70,71], which indicates that in the more stromal tumors, these splicing regulators are overexpressed and tend to bind downstream of their target exons and promote their inclusion. We note that RBFOX1 and QKI were previously shown to physically interact with each other in order to regulate alternative splicing in mammary epithelial cells, thereby promoting an epithelial-to-mesenchymal transition (EMT) [62], and have also been associated with the mesenchymal-to-epithelial transition (MET) that occurs during fetal kidney development [40]. , and inclusion-level histograms (bottom) for the alternatively spliced genes FGFR2, PRMT2, and TPM2.…”
Section: Motif Enrichment Analysis Reveals Putative Rna Binding Prote...mentioning
confidence: 99%